A Direct DFT Trajectory Study of the Bis-superoxo FAl(O2)2 Ionization - Cobos, Carlos Jorge (2008)
Direct density functional theory (DFT) classical trajectory calculations show that after bis-superoxo FAl(O2)2 ionization, one of the side-on dioxygen units undergoes a fast intramolecular rearrangement generating a stable radical cation which presents both a peroxo and a peroxyl group bound to the central Al atom, FAl(O2)OO +. Molecular properties of this predicted novel species have been estimated at the B3PW91/6-3l1+G(3df) and G3B3 levels of theory.